Determinants of Employee Performance during COVID-19 Pandemic in Indonesia - Meidilisa, Velia; Handika, Rebi Fara (AMAR (Andalas Management Review), 2022)
This study examines the impact of job insecurity, job stress and work engagement on job performance among Indonesian workers during the COVID-19 pandemic. The research applies a quantitative approach. A web-based survey collected the data from 146 workers in Indonesia from various sectors. The research hypotheses were tested using Partial Least Square – Structural Equation Modelling (PLS-SEM). The results showed that there are negative relationship between job insecurity and work engagement and also between job stress and job performance. Another result showed that there is positive relationship between work engagement and job performance. This study only conducted in Indonesia during COVID-19 pandemic. The study result will provide an understanding for company of employees’ needs of the clarity of their status. Such insight supports the development of employee maintenance in the future, especially among Indonesian workers. The massive implementation of workers layoff because of pandemic have increase the insecurity level for Indonesian workers. This study contributes to the organizational behavior and human resources management literature by testing factors like job insecurity, job stress and work engagement on job performance.